2006
DOI: 10.1002/chin.200627276
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ionizing Radiation to Environment Protection

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…The diagram of the test system is shown in Figure 3 and results are shown in Figure 4. The data were DE-EE0003494 consistent with prior published work [2][3][4][5][6][7][8] and confirmed that it is important to characterize the electron beam oxidation for the family of compounds that will be used in the final application if absolute destruction efficiencies are to be determined. Note that, within a compound family, relative destruction efficiency (i.e., ease of oxidation) increases with increasing molecular complexity.…”
Section: Previous Experiments By Aebsupporting
confidence: 83%
See 1 more Smart Citation
“…The diagram of the test system is shown in Figure 3 and results are shown in Figure 4. The data were DE-EE0003494 consistent with prior published work [2][3][4][5][6][7][8] and confirmed that it is important to characterize the electron beam oxidation for the family of compounds that will be used in the final application if absolute destruction efficiencies are to be determined. Note that, within a compound family, relative destruction efficiency (i.e., ease of oxidation) increases with increasing molecular complexity.…”
Section: Previous Experiments By Aebsupporting
confidence: 83%
“…Typical dose requirements for VOC/o-HAP oxidation by electrons are 5 to 15kGy. [4][5][6][7] For a fixed energy, increased dose is applied by increasing the electron current that is drawn from the filament and delivered through the emitter window.…”
Section: Thermal Energy Versus Electron Energymentioning
confidence: 99%
“…It should be noted that in some cases, it is very hard to determine if the reaction is electron transfer or radical addition/elimination. Successive reduction of Cr species from (VI) state to (III) state is achieved via reaction with H [32]. On the other hand, cadmium (II) and lead (II) are reduced via reaction with H or/and e − aq (Equation (10)) to produce Cd(I) that undergoes disprotonation (Equation (11)) or oxidization through a reaction with OH − or H2O2 (Equation (12)), or react with hydrogen to produce unstable MH + species that decay (Equation (13)) [18].…”
Section: Decomposition and Removal Mechanismsmentioning
confidence: 99%
“…To reduce the oxidation effect and subsequently to enhance cadmium and lead precipitation, an organic OH − scavenger could be used or the process could be operated in the absence of oxygen [31][32][33]. Ionizing radiation can reduce various forms of mercury via reaction with e − aq (Equation (5)) and H (Equation (6)) to form unstable compound that dimerized (Equation (7)) to produce insoluble form [31,32].…”
Section: Decomposition and Removal Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation